Sperm cell purification from mock forensic swabs using SOMAmer™ affinity reagents. (July 2018) - Katilius, Evaldas; Carmel, Andrew B.; Koss, Heidi; O'Connell, Dan; Smith, Breanna C.; Sanders, Glenn M.; LaBerge, Greggory S.
Highlights: A novel sperm capture methodology has been developed using SOMAmer affinity reagents. This work is a proof of concept that SOMAmers can be used to purify sperm from female cells in mixed body fluid evidence. This method has comparable sperm capture efficiency to a commercially available differential extraction kit. When adapted to robotic systems or automated, this approach could enable faster sperm isolation and separation. Abstract: We have demonstrated a proof of concept with affinity-based purification of sperm cells from mock forensic samples using SOMAmer™ reagents, DNA-based affinity reagents developed by SomaLogic, Inc. SOMAmer reagents were selected in vitro using whole-cell SELEX to bind specifically with intact, detergent-treated sperm cells. Successful separation of sperm from epithelial cells and their debris was demonstrated using buccal swabs with added semen. Primarily male DNA profiles were generated from sperm cells eluted from the types of cotton swabs typically used for rape kit evidence collection. The quality of sperm DNA isolated from samples purified using SOMAmers is comparable to existing commercially available differential extraction-based methods at higher sperm concentrations. This purification method is simple, offers relatively rapid (<2hr) sperm purification, and can potentially be automated using robotic workstations. This work serves as proof of concept that demonstrates the first use of SOMAmer reagents as affinity ligands to bind sperm cells. With further development, this technique can potentially be used for high-throughput sexual assault forensic casework.